Advancing Science by Enhancing Learning in the Laboratory (ASELL) : final report. - Kable, Scott; Buntine, Mark; Yeung, Alexandra; Sharma, Manjula; Lim, Kieran; Pyke, Simon; Burke da Silva, Karen; Barrie, Simon (Australian Learning and Teaching Council (ALTC), 2012)
Good laboratory programs play a major role in influencing student learning and performance. The laboratory program can be pivotal in defining a student's experience in the sciences, and if done poorly, can be a major factor contributing to disengagement from the subject area. The challenge remains to provide students with laboratory activities that are relevant and engaging and which offer effective learning opportunities. The Advancing Science by Enhancing Learning in the Laboratory (ASELL) project provides a multi-institutional, collaborative approach for improving the quality of undergraduate laboratories and providing effective professional development for academic staff. About 15,000 student surveys were received over the life of the project. Almost 100 academic staff in biology, chemistry and physics had professional development through attendance at an ASELL workshop during the life of the project. Following the workshops, the participants continued to evaluate, develop and improve both individual experiments and whole lab programs in their home institutions, with mentoring by the project team. Student evaluations of lab programs using the ASELL approach improved significantly. Over 100 ASELL-tested experiments in biology, chemistry and physics are available on the website, plus publications, templates and guidelines. This is the final report from the project.